Soft robotics to enhance upper limb endurance in individuals with multiple sclerosis - Lotti, Nicola; Missiroli, Francesco; Galofaro, Elisa; Tricomi, Enrica; Di Domenico, Dario; Semprini, Marianna; Casadio, Maura; Brichetto, Giampaolo; De Michieli, Lorenzo; Tacchino, Andrea; Masia, Lorenzo (Soft Robotics, 2024)
Multiple sclerosis (MS) is a chronic autoimmune disorder that affects the central nervous system and can result in various symptoms, including muscle weakness, spasticity, and fatigue, ultimately leading to the deterioration of the musculoskeletal system. However, in recent years, exosuits have emerged as a game-changing solution to assist individuals with MS during their daily activities. These lightweight and affordable wearable robotic devices have gained immense popularity. In our study, we assessed the performance of an elbow exosuit on eight individuals with MS using high-density electromyography to measure biceps muscle activity. The results demonstrated that our prototype significantly reduced muscle effort during both dynamic and isometric tasks while increasing the elbow range of motion. In addition, the exosuit effectively delayed the onset of muscle fatigue, enhancing endurance for people with MS and enabling them to perform heavy duty tasks for a longer period.
Gesehen am 06.08.2024